Penguatan Kapasitas Pengrajin Bata Melalui Pemanfaatan Lumpur Banjir Aceh dalam Produksi CSEB di Desa Lancang Barat Kecamatan Dewantara - Teuku Budi Aulia; Akhyar Akhyar; Nafisah Al-Huda; Wahyu Rinaldi; Hamidah Mohd Saman; Warid Wazien Ahmad Zailani; Jitendra Bothara; Muhammad Andri Putra; Andrian Kaifan (Universitas Pahlawan Tuanku Tambusai, 2026)
Conventional fired-clay brick production in Lancang Barat Village, Dewantara District, North Aceh Regency, continues to face challenges, including high energy consumption, inconsistent product quality, and the underutilization of Aceh flood sediment and rice straw waste. This community service program aimed to enhance the capacity of local brickmakers through the transfer of Compressed Stabilized Earth Block (CSEB) production technology using Aceh flood sediment and rice straw fibers as sustainable construction materials. A participatory approach was employed, consisting of community outreach, training, technology demonstrations, hands-on production practice, technical assistance, basic quality testing, and evaluation through pre-tests, post-tests, and participant satisfaction questionnaires. The program resulted in improved knowledge and technical skills among participants, the development of training modules and Standard Operating Procedures (SOPs), the establishment of a group of brickmakers capable of independently operating the technology, and the production of interlocking CSEBs that met the basic requirements for non-structural construction. The program also promoted circular economy practices through the utilization of local waste resources, reduced dependence on fired-clay bricks, and demonstrated strong potential for replication in other regions with similar characteristics.